G21(P) Acute pain treatment in a paediatric hospital setting: working towards understanding education needs and an algorithm for referral to the specialist pain services. (27th April 2015) - Beckett, K; Henderson, E; Stoddart, P; Parry, S; Fletcher, M
Abstract : Aims: Pain management has become more complex. Referral to specialist pain teams is commonplace in many children's services. This paper reports on a review undertaken with 2 aims: 1) assess how patients' pain was managed before, after and without specialist intervention, to identify non-specialised staff education needs regarding routine and non-routine pain management; 2) develop supporting evidence to inform an algorithm promoting appropriate referral of children needing more complex pain management to the pain service. Methods: Prospective notes and treatment chart review and real time logging of referrals of all patients referred prospectively to an acute paediatric pain service during a two week period in September 2013. Comparison data were extracted from patients not referred but likely to have similar pain management needs during the timeframe. =Patient history, drug therapy and pain scores were extracted. Following the review, semi-structured interviews were conducted with a range of clinical staff responsible for managing children's pain to explore their perspectives and local contextual factors aiding or preventing optimal pain management. Results: Fifteen patients were referred to the service. The majority were post-surgery and prescribed patient or nurse controlled analgesia or epidural infusion. Such referrals tended to be to address unresolved pain. In general, of the 15 cases and 15 comparisons, referrals /non referral were appropriate and there was little indication of over-reliance on the pain team or inappropriate access. Detail from the cases will be examined with respect to the insight they provide to pain management, service delivery and staff awareness. From the interviews it was clear that despite this finding, reflecting an unusually quiet period, there are structural and organisational issues which can cause lack of clarity about the role and remit of the team. Conclusion: The data reveal a problem found where services have evolved from a need which has changed over time with the team in a static state. Since review, the service has developed, reflecting the uncertainties and concerns of staff interviewed. Reflection on the purpose and provision, and observation of, a specialised service can help ensure it remains fit for purpose and specific concerns allowed to surface.